2015
DOI: 10.5603/cj.a2014.0101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin converting enzyme inhibitors on periprocedural myocardial infarction in patients with metabolic syndrome

Abstract: Background: Metabolic syndrome (MetS) has been reported as a risk factor for cardiovascular events. The aim of the present study is to investigate the association between chronic angiotensin-converting enzyme inhibitors (ACE-I) therapy and the rate of periprocedural myocardial infarction (PMI) after elective coronary stenting among patients with MetS. Methods: The inclusion criteria were MetS and plan for elective percutaneous coronary intervention. To assess the effect of ACE-I treatment on the incidence of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Recently, one prospective, although observational study, showed that chronic ACE inhibition therapy of MS+ patients can reduce the risk of periprocedural myocardial infarction compared with the ACE inhibitor naive group. 19 All these findings taken together strengthen the recommendations of current guidelines, which indicate that ACE inhibitors and angiotensin II-AT1 receptor blockers as the preferred treatment for high-risk patients. 20 , 21 …”
Section: Discussionsupporting
confidence: 64%
“…Recently, one prospective, although observational study, showed that chronic ACE inhibition therapy of MS+ patients can reduce the risk of periprocedural myocardial infarction compared with the ACE inhibitor naive group. 19 All these findings taken together strengthen the recommendations of current guidelines, which indicate that ACE inhibitors and angiotensin II-AT1 receptor blockers as the preferred treatment for high-risk patients. 20 , 21 …”
Section: Discussionsupporting
confidence: 64%